A Glimpse into the Lives of Mothers and their Children in a Homeless Shelter: What has Changed Over the Decades? - Warsi, Sadia (Journal of the American Academy of Special Education Professionals, 2006)
The main purpose of this study was to explore the impact of shelter living on the daily lives of families at the shelter. Results of this study parallel findings from past studies that suggest that issues of public parenting, availability of childcare options, shelter rules and regulations, loss of social networks and the desire to have a home were some of the issues raised by families living in shelters.